Effects of physical exercise intervention on improving physical functioning and quality of life among geriatric population. (A systematic review of randomized controlled trials) - Shoukat, Filza; Rehman, Syed Shakil Ur; Ashfaq Ahmed (Journal of the Pakistan Medical Association, 2024)
Objective: To assess the effectiveness of exercise intervention on elderly population's physical functioning and quality of life. Method: The systematic review was conducted in line with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, and comprised research on Cochrane Library, PubMed, Physiotherapy Evidence Database and Web of Science for randomised controlled trials published in the English language from January 2012 to December 2021. The trials included comprised individuals of either gender aged 60 years who were either community-dwelling elderly or patients living in residential facilities who could walk independently with or without assistive devices. Key words used for the search included age, exercise, physical function, quality of life and cognition. A 10-point scale from the Physiotherapy Evidence Database was used for methodological evaluation. Results: Of the 1050 studies initially found, 14(1.33%) were analysed in detail. All 14(100%) included multi-component exercise interventions, like aerobic, strength and balance, 4(28.6%) trials included cognition and quality of life as well. Only 1(7.14%) trial showed little or no improvement in terms of quality of life. Of the 2(14.3%) studies that reported the effects of exercise on falls, 1(50%) found positive impact of exercise interventions, while 1(50%) showed no improvement on the risk of fall and psychosocial factors related to fall. Overall, 9(64.3%) trials investigated the effects of exercise training on several aspects of mobility, and showed marked improvement in mobility. ---Continue